Effect of Liquid Salt Bath Nitrocarburizing on Mechanical Properties of Low-Alloy Sintered Steels - Serrai, S.; Mechachti, S.; Benchiheub, O.; Boudebane, S.; Fellah, M.; Touhami, M.Z. (Металлофизика и новейшие технологии, 2018)
The purpose of this study is to produce Fe–2Cu–2Ni–0.7Mo–XC steels by means of the powder metallurgy at different sintering temperatures. The mechanical properties of sintered steels have recently reached a level equivalent to that of steels produced by other processes. The static and dynamic mechanical properties of parts made of sintered steel depend on density and microstructure. Many process parameters such as initial composition, alloying elements, atmosphere, time, sintering temperature, and nitrocarburizing influence the microstructure of steel parts. The compacts’ preparation involves powder mixing, cold pressing at 500 MPa, and sintering at 1250°C within the H2 atmosphere for 2 hours and 25 min. The influence of sintering temperature on both hardness and microstructure of the steel is investigated. In this study, sintered Fe–2Cu–2Ni–0.7Mo–XC-type steels are developed. The impact of nitrocarburizing on this structure is evaluated. Microscopy, SEM, and destructive testing are used for characterization of the sintered steels. Метою даної роботи є одержання сталей типу Fe–2Cu–2Ni–0,7Mo–XC методами порошкової металурґії за різних температур спікання. Механічні властивості спечених сталей нещодавно сягнули рівня, аналогічного рівню сталей, що виробляються іншими методами. Статичні та динамічні механічні властивості деталів із спеченої сталі визначаються густиною та мікроструктурою. При цьому велика кількість характеристик процесу, наприклад, вихідний склад, леґувальні елементи, атмосфера, час, температура спікання та нітроцементація впливають на мікроструктуру сталевих деталів. Виготовлення пресованого матеріялу потребує змішування порошку, холодного пресування при 500 МПа та спікання при температурі у 1250°C в атмосфері Н22 протягом 2 годин 25 хв. Було досліджено вплив температури спікання на твердість і мікроструктуру сталі. В даній роботі було розглянуто сталі типу Fe–2Cu–2Ni–0,7Mo–XC. Було проведено оцінку впливу нітроцементації на такі структури. Для характеризації спечених сталей використовувалися мікроскопія, СЕМ та випробування на руйнування. Целью данной работы является получение сталей типа Fe–2Cu–2Ni–0,7Mo–XC методами порошковой металлургии при различных температурах спекания. Механические свойства спечённых сталей недавно достигли уровня, аналогичного уровню сталей, производимых другими методами. Статические и динамические механические свойства деталей из спечённой стали определяются плотностью и микроструктурой. При этом большое количество характеристик процесса, например, исходный состав, легирующие элементы, атмосфера, время, температура спекания и нитроцементация, влияют на микроструктуру стальных деталей. Изготовление прессованного материала требует смешивания порошка, холодного прессования при 500 МПа и спекания при температуре 1250°C в атмосфере Н22 в течение 2 часов 25 мин. Было исследовано влияние температуры спекания на твёрдость и микроструктуру стали. В данной работе были рассмотрены стали типа Fe–2Cu–2Ni–0,7Mo–XC. Была проведена оценка влияния нитроцементации на такие структуры. Для характеризации спечённых сталей использовались микроскопия, СЭМ и испытания на разрушение.